Intravitreal Administration of rhNGF Enhances Regenerative Processes in a Zebrafish Model of Retinal Degeneration - Cocchiaro, Pasquale; Di Donato, Vincenzo; Rubbini, Davide; Mastropasqua, Rodolfo; Allegretti, Marcello; Mantelli, Flavio; Aramini, Andrea; Brandolini, Laura (Frontiers in Pharmacology, 2022)
Nerve growth factor (NGF) is the best characterized neurotrophin, and it is known to play an important role in ocular homeostasis. Here, we demonstrated the expression of NGF receptors in adult zebrafish retina and optimized a light-induced retina degeneration (LID) zebrafish model that mimics human cone-rod disorders, demonstrating that intravitreal (IV) administration of rhNGF can boost zebrafish retinal regeneration in this model. Adult zebrafish retinae exposed to 60 h of light irradiation (60 h LID) displayed evident reduction of outer nuclear layer (ONL) thickness and cell number with presence of apoptotic cells. Retinal histologic evaluation at different time points showed that IV therapeutic injection of rhNGF resulted in an increase of ONL thickness and cell number at late time points after damage (14 and 21 days post injury), ultimately accelerating retinal tissue recovery by driving retinal cell proliferation. At a molecular level, rhNGF activated the ERK1/2 pathway and enhanced the regenerative potential of Müller glia gfap- and vim-expressing cells by stimulating at early time points the expression of the photoreceptor regeneration factor Drgal1-L2. Our results demonstrate the highly conserved nature of NGF canonical pathway in zebrafish and thus support the use of zebrafish models for testing new compounds with potential retinal regenerative properties. Moreover, the pro-regenerative effects of IV-injected NGF that we observed pave the way to further studies aimed at evaluating its effects also in mammals, in order to expedite the development of novel rhNGF-based therapeutic approaches for ophthalmological disorders.